1943
DOI: 10.1037/h0060357
|View full text |Cite
|
Sign up to set email alerts
|

The auditory acuity of preadolescent monkeys.

Abstract: Within the last few years a number of investigators have studied a variety of psychological functions in the monkey-indeed, the monkey is becoming a preferred animal in audition and other fields. Yet although "hearing" is a factor in many psychological tests with monkeys, the most basic auditory function, namely, the intensity threshold, of the monkey is not very precisely known, while other important functions, such as pitch and intensity discrimination, are enitrely uninvestigated.This study is in inquiry, u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
1

Year Published

1960
1960
2009
2009

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 7 publications
0
24
1
Order By: Relevance
“…Many investigators (Bragg and Dreher, 1969;Clack and Herman, 1963;Harris, 1943) are of the opinion that data obtained when the reinforcer is an aversive stimulus are more reliable than those obtained when the reinforcer is an appetitive stimulus; other experimenters (Stebbins, 1970a, Stebbins, 1971 These results suggest that sensory data are not influenced by the type of reinforcer used to maintain behavior during testing. The procedural difficulties and data discrepancies reported in other studies may have been a function of the reinforcement contingencies and behavior stability criteria, rather than stemming from inherent properties of the reinforcer.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…Many investigators (Bragg and Dreher, 1969;Clack and Herman, 1963;Harris, 1943) are of the opinion that data obtained when the reinforcer is an aversive stimulus are more reliable than those obtained when the reinforcer is an appetitive stimulus; other experimenters (Stebbins, 1970a, Stebbins, 1971 These results suggest that sensory data are not influenced by the type of reinforcer used to maintain behavior during testing. The procedural difficulties and data discrepancies reported in other studies may have been a function of the reinforcement contingencies and behavior stability criteria, rather than stemming from inherent properties of the reinforcer.…”
Section: Discussionmentioning
confidence: 89%
“…One view receiving considerable support (Bragg and Dreher, 1969;Clack and Herman, 1963;Mitchell, Gillette, Vernon, and Herman, 1970;Mitchell, Vernon, and Herman, 1971) was advanced by Harris (1943). Harris pared the effectiveness of his aversive control technique with an appetitive procedure used by Wendt (1934) and concluded that aversive stimuli provide a more efficient means of conditioning behavior and collecting reliable data.…”
mentioning
confidence: 99%
“…(Beecher 1974a;Fujita and Elliot 1965;Green 1971); Macaca fascicularis (Fujita and Elliot 1965;Stebbins et al 1966); M. fuscata (Jackson et al 1999;Owren et al 1988;Smith and Olszyk 1997); and M. mulatta (Behar et al 1965;Bennett et al 1983;Clack;1966;Clack and Herman 1963;Dalton 1968;Dalton et al 1969;Fujita and Elliot 1965;Harris 1943;Lasky et al 1999;LonsburyMartin and Martin 1981;Pfingst et al 1975Pfingst et al , 1978Wendt 1934). For the comparisons of Macaca mulatta, I modified or excluded several of the audiograms.…”
Section: Effects Of Transducer Type and Conditioning Proceduresmentioning
confidence: 94%
“…They used behavioral conditioning to determine absolute auditory thresholds (lowest detectable level) in chimpanzees and several species of monkeys, respectively. Researchers generally consider auditory thresholds the most fundamental measure of hearing performance (Harris 1943;Heffner 2004;Jackson et al 1999;Lonsbury-Martin and Martin 1981;Stebbins 1975), though they have also investigated other parameters of hearing sensitivity such as localization ability and frequency and amplitude discrimination in a handful of species. Here, hearing sensitivity refers solely to differences in absolute auditory thresholds.…”
Section: Introductionmentioning
confidence: 99%
“…But latencies also increase near the threshold. Harris (2), in his study of auditory acuity of monkeys, used this latter effect to simplify his testing procedure.…”
Section: Introductionmentioning
confidence: 99%